ChemInform Abstract: Understanding Ceria‐Based Catalytic Materials: an Overview of Recent Progress. Issue 16 (22nd April 2014) - Delgado, Juan Jose; del Rio, Eloy; Chen, Xiaowei; Blanco, Ginesa; Pintado, Jose Maria; Bernal, Serafin; Calvino, Jose Juan
Abstract Review: 393 refs.